Effects of different mind-body exercises on pain in patients with knee osteoarthritis: A pairwise, network, and dose-response meta-analysis - Bei Wu; Wenyu Liu; Shuang Wang; Huimin Li; Meng Yin (Complementary Therapies in Medicine)
Background: Osteoarthritis (OA) is a common chronic disease that leads to chronic pain, limited mobility, and reduced quality of life for patients. In recent years, mind-body exercise (e.g., yoga, tai chi, etc.) has been gradually recognized as a comprehensive intervention with positive effects on pain relief and improved function in arthritis patients. However, the evidence on the effect of mind-body exercise on pain relief in arthritis patients is inconsistent, and this meta-analysis aimed to assess the combined effect of mind-body exercise in reducing pain in patients with knee OA. Methods: A systematic search using MEDLINE, Embase, Cochrane Library, and Webof Science was conducted from the beginning of the respective database information until December 2024, to identify randomized controlled trials (RCTs) on the effects of mind-body exercises on outcomes in patients with knee OA. Pairwise and dose-response meta-analyses were performed using Bayesian hierarchical random-effects models to analyze these effects. Cochrane Risk of Bias tool was used to assess the risk of bias of the included studies, and CINeMA was used to evaluate the confidence of the results. Results: A total of 13 RCTs involving 558 participants were included in this study. The average age of participants ranged from 61 to 76 years. Mind-body exercise therapies had a small-to-moderate effect on pain compared to no-intervention controls (Hedges' g = −0.35). Among the mind-body exercise types, tai chi (Hedges' g = −0.41) had the greatest effect on pain levels, followed by yoga (Hedges' g = −0.38) and qigong (Hedges' g = −0.26). Of the 13 studies, eight were categorized as high risk of bias, with the main risk of bias coming from blinded implementation and selective reporting issues. Furthermore, the credibility of all mind-body exercises was extremely low owing to serious within-study bias and several other concerns Conclusion: Mind-body exercise had a small to moderate effect on pain relief in patients with knee OA, with tai chi being the most effective, followed by yoga and qi gong. The mind-body exercise dose is clinically significant when it reaches 250–610 MET-min. Sex and age may affect treatment effects, with women responding more significantly to tai chi. Due to the limitations of risk of bias and low confidence level, future studies should expand the sample size, conduct strict blinding control, etc. to improve the reliability and applicability of research evidence. PROSPERO registration number: CRD42024585874